(untitled) (ModaPalavra e-periódico, 2020)
The designer’s design practice is associated with the development of a collection, which goes through several stages until its materialization and availability in the market. Thus, in order to coordinate its creation, it is important to apply a methodology that helps and systematizes the entire process of developing the clothing product. In this way, this article aims to apply the Guidance Guide for the Development of Projects (GODP), in the des ign practice of Fashion Design. For that, the applied, qualitative descriptive research was used, through a bibliographical research. Initially, studies were carried out on the garment collection development process and following these procedures were appl ied in the GODP methodology. The results show that the GODP applied to the design practice of fashion design can help the designers to understand the real needs of the users and to manage the operational process of the collection of clothing. However, usin g a user - centered methodology in the fashion design practice allows the collection of information relevant to the project, as well as raising data about the target audience, which favors the comfort, safety and usability of clothing